Characterization of two newly isolated Staphylococcus aureus bacteriophages from Japan belonging to the genus Silviavirus - Kitamura, Naoya (Arch Virol, 2020)
Two Staphylococcus aureus bacteriophages, KSAP7 and KSAP11, were isolated from sewage and characterized. Based on morphology and DNA sequences, they were assigned to the genus Silviavirus, subfamily Twortvirinae, family Herelleviridae, whose members are hypothesized to be suitable for bacteriophage therapy. The KSAP7 and KSAP11 genomes were 137,950 and 138,307 bp in size, respectively. Although their DNA sequences were almost identical, evidence of site-specific DNA rearrangements was found in two regions. Changes in the number of PIEPEK amino acid sequence repeats encoded by orf10 and the insertion/deletion of a 541-bp sequence that includes a possible tail-related gene were identified. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00705-020-04749-6) contains supplementary material, which is available to authorized users.